Effects of Non-Newtonian Parameter on Unsteady MHD Oscillatory Slip Flow of Viscoelastic Fluid in a Planer Channel (MATEMATIKA, 2014)
An analysis has been carried out to obtain the eﬀect of the non-Newtonian parameter on the problem of magnetohydrodynamic (MHD) mixed convective oscillat- ory ﬂow of an electrically conducting optically thin viscoelastic ﬂuid through a planer channel ﬁlled with saturated porous medium in the presence of a ﬁrst-order chemical reaction. The eﬀect of buoyancy, heat source, thermal radiation, and chemical reaction are taken into account embedded with slip boundary condition, varying temperature and concentration. The closed form analytical solutions are constructed for the prob- lem. The eﬀects of the magnetic ﬁeld, porous parameter, solutal and thermal Grashof numbers on velocity proﬁle for diﬀerent values of the non-Newtonian parameter are illustrated with the help of ﬁgures. A table containing the numerical data for skin friction is also provided. Keywords : viscoelastic ﬂuid; chemical reaction; MHD; oscillatory ﬂow. 2010 Mathematics Subject Classiﬁcation 76A10; 76W05.